2015
DOI: 10.1007/s10661-015-4389-6
|View full text |Cite
|
Sign up to set email alerts
|

The determination of physiological and DNA changes in seedlings of maize (Zea mays L.) seeds exposed to the waters of the Gediz River and copper heavy metal stress

Abstract: In this study, the effects of the heavy metal-polluted waters of the Gediz River, which flow into the Aegean Sea, and different concentrations of copper (Cu) solutions on maize (Zea mays L.) seedlings are investigated with physiological parameters and random amplified polymorphic DNA (RAPD) assay. Results displayed physiologically a significant difference in root and stem length between the control seedlings and the seedlings grown with the waters of the Gediz River. Also, the certain ascending concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This is explained by the direct influence of copper on the formation of reactive oxygen species [superoxide radical (O 2˙À ), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OHÀ)] because it is a trace element. Since copper and iron transition metals are involved in oxidoreduction reactions, they act as catalysts that accelerate the formation of reactive oxygen species [63][64][65][66]. As in previous studies, it was found that artichoke seedlings are negatively affected mostly by copper in molecular terms [39,41,67,68].…”
Section: Discussionmentioning
confidence: 75%
“…This is explained by the direct influence of copper on the formation of reactive oxygen species [superoxide radical (O 2˙À ), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OHÀ)] because it is a trace element. Since copper and iron transition metals are involved in oxidoreduction reactions, they act as catalysts that accelerate the formation of reactive oxygen species [63][64][65][66]. As in previous studies, it was found that artichoke seedlings are negatively affected mostly by copper in molecular terms [39,41,67,68].…”
Section: Discussionmentioning
confidence: 75%
“…They observed a total of 169 reproducible bands using 12 primers, ten of which yielded polymorphisms, pointing out a clear genotoxic effect caused by the metals. Batir et al [43] determined the effect of different concentrations of copper (Cu) solutions on maize (Zea mays L.) seedlings by using physiological parameters and RAPD analysis. In this study revealed band increase and or loss in the RAPD profiles of the samples.…”
Section: Discussionmentioning
confidence: 99%